Rodzaje systemów opieki zdrowotnej a wydatki na ochronę zdrowia w wybranych krajach Unii Europejskiej - Kaczmarek-Wysocka, Jarosława; Świderska, Jolanta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In many countries financing health care is becoming more and more complex. In order to compare the health care spending in various countries, it is necessary first to describe their managing systems. The author of the article chose 4 European countries (Poland, Great Britain, Netherlands, France) and subjected to analysis the expenses on health care in that countries. The structure of the expenses has also been underlined. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 190-197